An immune artificial algorithm for dynamic optimization problems: a case of study - Aragón, Victoria S. (2009)
In this paper, we present an algorithm inspired on the T-Cell model of the immune system, i.e., an artificial immune system (AIS). The proposed approach (called DTC) is intented to solve dynamic optimiza- tion problems. We realize a first study and we validate our algorithm using dynamic functions taken from the specialized literature. Results are promising when we compare them with respect to the results obtained by five AIS representative of the state of the art in this field.